2012
DOI: 10.1155/2012/424285
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Cysteine Protects against Methamphetamine-Induced Dopaminergic Neurodegeneration via Modulation of Redox Status and Autophagy in Dopaminergic Cells

Abstract: Methamphetamine- (MA-) induced neurotoxicity is associated with mitochondrial dysfunction and enhanced oxidative stress. Our previous study demonstrated that MA induces autophagy in a dopaminergic neuronal cell model (N27 cells). The cellular mechanisms underlying MA-induced autophagy and apoptosis remain poorly characterized. In the present study we sought to investigate the importance of GSH redox status in MA-induced neurotoxicity using a thiol antioxidant, N-acetylcysteine (NAC). Morphological and biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…N-acetyl cysteine has been shown to reverse the activation of autophagy by neuregulin in prostate cancer cells, and also prevents the hypoxia induced autophagic cell death of retinal ganglion cells [202, 203]. In a methamphetamine-induced model of Parkinson’s disease in N27 cells, N-acetyl cysteine can prevent dopaminergic cell death by preventing the depletion of GSH and activating autophagy [204]. …”
Section: Oxidative and Nitrative Signals Regulate Autophagymentioning
confidence: 99%
“…N-acetyl cysteine has been shown to reverse the activation of autophagy by neuregulin in prostate cancer cells, and also prevents the hypoxia induced autophagic cell death of retinal ganglion cells [202, 203]. In a methamphetamine-induced model of Parkinson’s disease in N27 cells, N-acetyl cysteine can prevent dopaminergic cell death by preventing the depletion of GSH and activating autophagy [204]. …”
Section: Oxidative and Nitrative Signals Regulate Autophagymentioning
confidence: 99%
“…Given the important role of GSH in redox homeostasis, it is not surprising that changes in GSH and redox-sensitive enzymes have been found in vitro and preclinical and clinical studies of METH addiction. METH-induced autophagy and apoptotic cell death in the N27 dopaminergic neuronal cell model were accompanied by GSH depletion and increases in 3-nitrotyrosine and 4-hydroxynonenal [63]. Mice treated with METH have shown a decrease in GSH in the striatum, amygdala, hippocampus and frontal cortex [64].…”
Section: Drugs Of Abuse and Oxidative/nitrosative Stressmentioning
confidence: 99%
“…In addition, a decrease in DAT immunoreactivity was observed 7 days post-treatment, which was also attenuated by SMTC pretreatment [68]. NAC has provided protection against METH-induced dopaminergic neurodegeneration in vitro [63] and improved memory consolidation in METH-treated mice [64]. The NAC derivative and novel antioxidant, N -acetylcysteine amide (NACA), has shown to be protective against METH-induced oxidative stress in vitro [69].…”
Section: Drugs Of Abuse and Oxidative/nitrosative Stressmentioning
confidence: 99%
“…Shivalingappa et al found that MA treatment in N27 cells induces formation of 3-NT and 4-HNE in a DA-dependent mechanism at least partially attributed to MA's concurrent reduction in GSH levels relative to untreated controls. They additionally propose 3-NT may correspond to a prior increase in ONOO - where ONOO - can inhibit the DA transporter (Chandramani Shivalingappa et al, 2012). Supplementation with the antioxidant N-acetylcysteine (NAC) restored LPO product and antioxidant levels compared to untreated controls.…”
Section: Introductionmentioning
confidence: 99%